Ileo-psoas muscle metastasis from pulmonary carcinoma - S Parajuli; RB Basnet; A Tuladhar (Association of Clinical Pathologists of Nepal, 2012)
Metastatic disease to muscle is rare and may be misdiagnosed when it is the presenting symptom, particularly in the absence of a known primary tumor. Skeletal muscle metastasis as a mode of presentation of primary lung cancer is an unusual phenomenon. Here, we report a case of ileo-psoas muscle metastasis from lung cancer as the initial clinical manifestation in a 58 year-old male with a personal history of heavy smoking. Excisional biopsy of the mass in the ileo-psoas muscle revealed metastatic adenocarcinoma. Computed tomography scan of the chest for a primary search was done and found to be pulmonary carcinoma. DOI: http://dx.doi.org/10.3126/jpn.v2i3.6033 JPN 2012; 2(3): 251-253